Army Ice Cap Swing Takes 22 Days for Round Trip of 276 Miles - Polar R & D Center. Public Information Office, United States Army. (ARCTIC, 1962)
Describes monthly supply trips from Camp Tuto to Camp Century on the Greenland icecap. The supplies are carried in trains (swings) of 20-ton sleds pulled by low-ground-pressure D-8 and D-9 tractors. Tractor breakdowns and adverse weather conditions prolonged a winter 1961-62 trip, which is reported in some detail.